Balancing act: progress and prospects in breeding soybean varieties with high oil and seed protein content - Shi, Qingchi; Mo, Weiliang; Zheng, Xunan; Zhao, Xuelai; Chen, Xiaoyu; Zhang, Li; Qin, Jianchun; Yang, Zhenming; Zuo, Zecheng (Frontiers in Plant Science, 2025)
Soybean (Glycine max [L.] Merr.) serves as a critical global source of plant-based protein and oil, yet the inverse relationship between seed protein content (PC) and oil content (OC) remains a major barrier to simultaneous improvement. Recent advances in genomics, transcriptomics, and proteomics have elucidated key regulatory genes and networks underlying these traits, including GmWRI1a, LEC2, Glyma.20G085100, and the LAFL transcriptional module. These findings reveal that carbon and nitrogen resource partitioning during seed maturation is tightly coordinated by pleiotropic regulators, many of which mediate metabolic trade-offs that limit dual optimization. Although certain wild soybean loci and “bridge genes” like GmSWEET39 show potential to partially uncouple PC–OC antagonism, their effects are often context-dependent and modest in scale. This review synthesizes current understanding of the genetic architecture and metabolic frameworks that shape oil and protein accumulation in soybean seeds. It highlights promising molecular breeding strategies—including phase-specific gene regulation, CRISPR-mediated multiplex editing, and the stacking of favorable alleles—to overcome long-standing trade-offs. By leveraging multi-omics integration and functional VALidation in diverse germplasm, future soybean breeding programs can more effectively develop high-protein, high-oil cultivars tailored to both nutritional and industrial demands.